Does Chalcedon divide or unite?: towards convergence in orthodox christology - Verghese, Paul; Lazareth, William Henry; Nissiotis, Nikos A. (World Council of Churches, 1981)
The problem of the unification of the non-Chalcedonian churches of the East with the Orthodox on the basis of Cyril's formula / Johannes N. Karmiris -- St. Cyril's "One physics or hypostasis of God the Logos incarnate" and Chalcedon / John S. Romanides -- One incarnate nature of God the Word / V.C. Samuel -- Christology in the liturgical tradition of the Armenian Church / Mesrob K. Krikorian -- The Orthodox faith in the liturgies and prayers of the Coptic Church / Hakim Amin -- The Christological dogma and its terminology / Georges Florovsky -- Ecclesiological issues concerning the relation of Eastern Orthodox and Oriental Orthodox Churches / Paulos Mar Gregorious -- Ecclesiological issues inherent in the relations between Eastern Chalcedonian and Oriental non-Chalcedonian Churches / John D. Zizioulas